LACTIC ACID STUDY OF POST SLAUGHTERED ON PIGS IN ABBATOIR SANGGARAN DENPASAR BALI - Siswanto, Siswanto -; Soma, I Gede (Buletin Veteriner Udayana, 2022)
The lactic acid in blood and meat can accelerate rigor mortis and reduce the quality of the meat, because the meat will rot quickly, thereby reducing its selling power. Increased levels of lactic acid in the blood / meat can be caused by improper cutting processes. This study aims to see the levels of lactic acid in the blood as monitoring. The experimental animals were used by 30 healthy pigs slaughtered at the slaughterhouse in Sanggaran, Denpasar, Bali. Sampling was done purposively. The blood sample was taken as much as 3 ml from the jugular vein. Elisa method is used for determination of plasma lactic acid levels. The results showed the range of lactic acid levels was 2.10 - 2.95 mmol / dL with a mean of 2.47 mmol / dL, Sd. 0.22. These profiles are in normal condition so it is not noticed that the handling or management before and during cutting is good.